Hubungan Status Sosial Ekonomi Orang Tua dan Self Efficacy dengan Perilaku Merokok Elektrik (Vape) Pada Remaja di Beejie Cafe dan Andante Cafe - Kristamuliana; Ponimin, Litasya Glory Injilika; Simak, Valen Fridolin (Mapalus Nursing Science Journal, 2023)
Background. Adolescents are individuals who are easily influenced by their surroundings. With activities outside the house, adolescents will tend to do things that deviate due to a lack of supervision from their parents. Objective: To determine the relationship between socioeconomic status and self-efficacy and the behavior of electric smoking (vaping) in adolescents at Beejie Cafe and Andante Cafe. Method is a type of quantitative research, with a total of 107 research samples obtained through the Accidental Sampling method. The results of this study were obtained from the gamma correlation test. From this test, a value of p = 0.585 and a value of r = -0.099 were obtained for the socioeconomic status of parents with smoking behavior in adolescents, while for self-efficacy with smoking behavior in adolescents, a p value of 0.610 and a r value of -0.089 were obtained. Discussion. The low, medium, and high socioeconomic status of parents and low, medium, and high self-efficacy will still make adolescents use e-cigarettes (vape). Conclusion. Parents’ socioeconomic status and self-efficacy with smoking behavior in adolescents at Beejie Cafe and Andante Cafe have no relationship. Keywords: Socioeconomic, self-efficacy, smoking behavior, adolescence.